Extracellular Vesicles: Novel Mediators of Cell Communication In Metabolic Disease. (January 2017) - Huang-Doran, Isabel; Zhang, Chen-Yu; Vidal-Puig, Antonio
Abstract : Metabolic homeostasis emerges from the complex, multidirectional crosstalk between key metabolic tissues including adipose tissue, liver, and skeletal muscle. This crosstalk, traditionally mediated by hormones and metabolites, becomes dysregulated in human diseases such as obesity and diabetes. Extracellular vesicles (EVs; including exosomes) are circulating, cell-derived nanoparticles containing proteins and nucleic acids that interact with and modify local and distant cellular targets. Accumulating evidence, reviewed herein, supports a role for extracellular vesicles in obesity-associated metabolic disturbance, particularly the local and systemic inflammation characteristic of adipose and hepatic stress. As the practical and conceptual challenges facing the field are tackled, this emerging and versatile mode of intercellular communication may afford valuable insights and therapeutic opportunities in combatting these major threats to modern human health. Trends: Exosomes and other EVs containing protein and RNA are released continually and ubiquitously into the local tissue and circulation. An emerging property of exosomes is their ability to target and modify specific cells and tissues. Early evidence suggests that EVs released from adipose tissue may modulate distant metabolic tissues including liver, skeletal muscle, and pancreas. Such mechanisms may contribute to the development of obesity-associated insulin resistance, diabetes, and NAFLD. Within obese adipose tissue, EVs may carry metabolic signals between hypertrophied adipocytes and small, healthy adipocytes. They also appear to activate adipose tissue macrophages and endothelial cells, and thus may contribute to adipose tissue remodelling and local and systemic inflammation characteristic of obesity.